Case report of a mysterious myocardial mass: an aetiological conundrum. Issue 1 (22nd February 2018) - Stewart, Jack; Baltabaeva, Aigul; Beeton, Ian; Wignall, Oliver
Abstract: Introduction: Atypical chest pain is frequently an aetiological conundrum, and missing a diagnosis of underlying cardiac disease can have detrimental consequences. The investigation of this may rule out cardiac disease but often provides no clear answers to the underlying pathology. Case presentation: An 80-year-old man with a background of bilateral inguinal hernia repairs but no cardiac disease presented to his general practitioner with intermittent chest pain of approximately 15 min duration, felt inside his chest under his right nipple. His episodes of chest discomfort had increased in frequency, occurring both at rest and upon exertion. He was seen by the cardiology team at his local hospital and reassured following normal coronary angiography and outpatient echocardiography. The pain persisted, so cardiac magnetic resonance imaging (MRI) was arranged to exclude the underlying myocardial disease. This demonstrated a mass within the right ventricular free wall, which MRI was unable to characterize. Follow-up cardiac computed tomography showed this to be a metallic object within the right ventricular wall, but despite thorough examination of his medical and social history, there remains no obvious explanation to its aetiology other than potentially due to clip migration from his hernia repair. Discussion: Metallic foreign bodies within the myocardium are described in case reports but almost entirely in the setting of intentional self-injury. There is no previous case evidence of migration of distal surgical clips to the heart, but there appears to be no other clear aetiology for this gentleman's pathology, thus representing a novel description of iatrogenic injury.